Anakinra—An Interleukin-1 Receptor Antagonist for COVID-19. (22nd March 2023) - Nguyen, Timothy; Dima, Lorena; Willett, Kristine C.
Abstract : Background: Coronavirus disease (COVID-19) caused by SARS-CoV-2 virus caused a global pandemic in 2019. There are limited pharmacologic options available. The Food and Drug Administration initiated an emergency use authorization process to expedite pharmacologic agents to treat COVID-19. There are several agents available through the emergency use authorization process, ritonavir-boosted nirmatrelvir, remdesivir, and baricitinib. Anakinra is an interleukin (IL)-1 receptor antagonist that exhibits properties in fighting against COVID-19. Mechanism of Action, Pharmacodynamics, and Pharmacokinetics: Anakinra is a recombinant IL-1 receptor antagonist. The epithelial cell damage that may occur with COVID-19 enhances the release of IL-1, which plays a central role in severe cases. Thus, drugs that inhibit the IL-1 receptor may be beneficial in the management of COVID-19. Anakinra has good bioavailability after subcutaneous injection and a half-life of up to 6 hours. Clinical Trials: The SAVE-MORE, double-blind, randomized controlled trial, phase 3 evaluated the efficacy and safety of anakinra. Anakinra 100 mg was given subcutaneously daily for up to 10 days in patients with moderate and severe COVID-19 and plasma suPAR ≥6 ng/mL. Anakinra group had a 50.4% fully recovered with no viral RNA detected on day 28 versus 26.5% for placebo, and more than 50% of relative decrease in mortality. A significantly decreased risk of worse clinical outcome was observed. Therapeutic Advance: COVID-19 causes global pandemic and a serious viral disease. There are limited therapy options to combat this deadly disease. Anakinra is an IL-1 receptor antagonist and shown to be effective for the treatment of COVID-19 in some trials but not others. Anakinra, the first in this class, seems to have a mix result for the treatment of COVID-19.